1998
DOI: 10.1161/01.cir.98.5.458
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Relationship Between Electrode Size and Lesion Size During Radiofrequency Ablation With Active Electrode Cooling

Abstract: The smaller electrode resulted in transmission of a greater fraction of the radiofrequency power to the tissue and resulted in higher tissue temperature, larger lesions, and lower dependency of lesion size on the electrode orientation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
141
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(153 citation statements)
references
References 36 publications
9
141
1
2
Order By: Relevance
“…[12][13][14][15]19 In addition, experimental studies 20,21 and nonrandomized studies [12][13][14][15] Thus, ablation of typical AFL with an irrigated-tip catheter was recently recommended as first-line therapy. 22 Only 2 randomized studies demonstrated that both catheter techniques were equivalent, although several limitations were underlined.…”
Section: Comparison Between 8-mm-tip and Cooled-tip Cathetersmentioning
confidence: 99%
“…[12][13][14][15]19 In addition, experimental studies 20,21 and nonrandomized studies [12][13][14][15] Thus, ablation of typical AFL with an irrigated-tip catheter was recently recommended as first-line therapy. 22 Only 2 randomized studies demonstrated that both catheter techniques were equivalent, although several limitations were underlined.…”
Section: Comparison Between 8-mm-tip and Cooled-tip Cathetersmentioning
confidence: 99%
“…Furthermore, on the basis of the heating efficiency equation postulated for endocardial ablation, 14 one might expect RFA efficiency with active cooling to be even greater on the epicardial surface. That is, given equivalent catheter-tissue contact, a fixed amount of power delivery could result in greater tissue absorption during epicardial ablation because of the absence of current shunting by the bloodstream.…”
Section: Epicardial Cooled-tip Rf Ablationmentioning
confidence: 99%
“…Specifically, saline cooling of the ablation electrode by external irrigation is known to be an effective means of generating deep endocardial RF lesions. 14,18 But in the pericardial space, (1) irrigation of the electrode with saline, a conductive solution, may increase the size of the virtual ablation electrode to uncontrollable dimensions because of the absence of the dispersing "buffering" effect of the bloodstream, and (2) the volume of infused fluid into the pericardial sac may alter the biophysical properties of each successive ablation pulse, necessitating manual aspiration of the pericardial space before each lesion. Also, no information is available regarding the use of large-tip (eg, 8-mm tip) catheters for epicardial mapping and ablation.…”
Section: Potential Clinical Implicationsmentioning
confidence: 99%
“…Additionally, irrigation at the site of ablation has also helped to minimize thrombus formation at the ablation site as well. The saline used for irrigation can be circulated within the electrode (closed loop system), or open irrigation system that flushes saline through openings in the ablation electrode (Budde et al 1987, Grumbrecht et al 1998, Kongsgaard et al 1997, matsudairi et al 2003, Nakagawa et al 1998, Wittkampf et al 1989and Yokoyama et al 2006. A major limitation of this catheter is the poor correlation of the tip temperature with the tissue temperature, often resulting in RF being curtailed and therefore incomplete lesions are made.…”
Section: Irrigated Tip Electrode Cathetermentioning
confidence: 99%